CULTURE OF SANTRI SENIORITY BETWEEN TRADITION AND MODERNIZATION IN ISLAMIC BOARDING SCHOOL EDUCATION - Kamilia, Rizki; P, Damar Cahya; A, Ni’matus Silmi; F, Lailatul; Y, Siti Nafizah; Zakiyatul, Lutfi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The tradition of seniority in Islamic boarding schools plays an important role in shaping the social structure and character of santri, where senior santri have the authority to guide and supervise junior santri. This tradition is not only seen as a hierarchy, but also as a learning mechanism that teaches the values of respect, responsibility and leadership. Even though it provides benefits in character building, challenges arise regarding the potential for abuse of authority which can affect relationships between students. In an organizational context, seniority also plays a role in efficient decision making, but can hinder innovation if it is too rigid. In addition, modernization in Islamic boarding schools provides opportunities to improve the quality of education through technology, but risks eroding the traditional values that characterize Islamic boarding schools. Therefore, it is important to maintain a balance between modernization and preserving traditions, as well as integrating moral education to ensure seniority is carried out wisely and fairly. Through proper management, Islamic boarding schools can produce a generation of students who are not only academically intelligent, but also have strong morality and character, able to contribute positively to a society that is balanced between cultural heritage and the demands of the times.